The mechanical properties of tailing recycled aggregate concrete and its resistance to the coupled deterioration of sulfate attack and wetting–drying cycles. (October 2020) - Xu, Fan; Wang, Sheliang; Li, Tao; Liu, Bo; Li, Binbin; Zhou, Yuan
Abstract: This experimental research evaluated the feasibility of using iron ore tailings (IOTs) to produce tailing recycled aggregate concrete (TRAC). For this purpose, silica sand was replaced with different IOT contents (0%, 10%, 20%, 30%, 40%, 50%, 70% and 100%), and the corresponding performance was compared with that of natural aggregate concrete (NAC) and recycled aggregate concrete (RAC). The mechanical properties of the different concrete mixtures were investigated in terms of their compressive strength, splitting tensile strength, and relative dynamic elastic modulus (RDEM). The maximum principal strain and minimum principal strain, which were recorded with a digital image correlation (DIC) system, were also considered in this study. The influence of sulfate attack and wetting–drying (W–D) cycles on the samples was determined by analysing the corresponding changes in the mass, residual compressive strength and RDEM. The results illustrated that the incorporation of IOTs markedly enhanced the mechanical properties of RAC. However, when the IOT content increased to a certain extent, the concrete became brittle. In addition, the RAC containing 10% or 20% IOTs exhibited slightly better resistance to sulfate attack and W–D cycles than RAC without IOTs.